DISPARITAS PUTUSAN HAKIM DALAM PENJATUHAN PIDANA UANG PENGGANTI TERHADAP TERDAKWA TINDAK PIDANA KORUPSI - Wibowo, Agus Ari; Franciska, Wira; Ismed, Mohamad (SINERGI : Jurnal Riset Ilmiah, 2025)
The disparity in money substitutes reflects the empirical reality in the Indonesian justice system, namely how judges factually make decisions by considering various aspects, including juridical and sociological considerations. The research method used in this research is a normative juridical approach which is carried out as an effort to obtain the necessary data related to the problem. Data used with secondary data and tertiary legal materials. In addition, primary data is also used as a supporter of secondary data legal materials. For data analysis, a qualitative juridical analysis method is used. The results of the study that the implementation of money substitutes in corruption is based on Article 17 juncto Article 18 of law no. 31 of 1999 jo. UU No. 20 of 2001 and Perma No. 5 of 2014. Disparity in the decision of the judge in the imposition of criminal money substitutes can occur because the law only regulates the minimum and maximum limits without details of the type and severity of punishment, the absence of sentencing guidelines for judges, as well as differences in the flow of law adopted in passing the verdict.